RELIABILITY’S ESTIMATION OF INTERMODAL CONTAINER TRANSPORTATION IN THE SUPPLY CHAINS: Array - , Є. В., О. О. (Municipal economy of cities. Series: «Economy science», 2018)
Participation of Ukraine in the International Association "Trans-Caspian International Transport Route" sets the directions for the development of intermodal transportation. The literature analysis revealed deficiencies of the considered approaches and the proposed criteria. The issue of development of tools for quality management of services in the organization of intermodal container transportation was becoming topical. The approach to reliability’s estimation of the intermodal container transportation system have been proposed. It bases on the definition of a complex integral reliability index. The task of efficient management of the quality of transport services is to optimize the time of movement of containers from the consignor to consignee due to the uninterrupted functioning of each element of the supply chain. This is achieved by minimizing and eliminating the delay time of the container traffic in the system. The method of the reliability’s estimation of the containers transportation process of five stages have been offered. It will allow operators of intermodal container transportation to form a profile of rational strategies for transport services of cargo owners in supply chains when making management decisions. The optimum level of reliability of containers delivery on the international route China - the EU countries as on modules and in the whole on the system have been determined, with the application of the profile of rational strategies in accordance with the requirements of the cargo owners. When forming strategies for the organization of transport services, it must be taken into account that an increasing of the reliability of the functioning of system's elements can lead to costs increasing of delivery in the conditions of budget restriction. Implementation of the approach will allow maintaining an appropriate level of quality and improving the efficiency of transport services in the organization of intermodal container transportation in the supply chain in accordance with the requirements of the cargo owner. Keywords: container, intermodal transportation, reliability, estimation, the supply chain.